2018
DOI: 10.1186/s40001-018-0332-y
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction after hook plate treatment of bony avulsion fracture of the distal phalanges

Abstract: BackgroundBony avulsion fractures of the distal phalanges can result in mallet finger deformity if not treated appropriately. Therefore, only minimally displaced fractures can be treated conservatively with a good outcome, as dislocation occurs very often. Several surgical treatment options have been developed during the past decades. Data concerning the recently developed hook plate are promising. So far, no data concerning the subjective satisfaction with this method have been published. Therefore, we have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The bony mallet thumbs can be surgically treated with tension band technique, pull-in suture, extension block pinning with one or two Kirschner wires, hook plate, screw, external fixation, compression pins, and biodegradable device. 9 In a recent study by Vester et al, treatment by hook plate technique was reported as a reliable and safe method to treat bony avulsion fractures of the distal phalanx, with high patient satisfaction. 9 But the esthetic aspects and the nail deformities are more challenging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The bony mallet thumbs can be surgically treated with tension band technique, pull-in suture, extension block pinning with one or two Kirschner wires, hook plate, screw, external fixation, compression pins, and biodegradable device. 9 In a recent study by Vester et al, treatment by hook plate technique was reported as a reliable and safe method to treat bony avulsion fractures of the distal phalanx, with high patient satisfaction. 9 But the esthetic aspects and the nail deformities are more challenging.…”
Section: Discussionmentioning
confidence: 99%
“… 9 In a recent study by Vester et al, treatment by hook plate technique was reported as a reliable and safe method to treat bony avulsion fractures of the distal phalanx, with high patient satisfaction. 9 But the esthetic aspects and the nail deformities are more challenging. 9 In our presented patient, however, no nail deformity occurred with the screw, which seemed to be due to the large size of the bony fragment with stable fixation and lack of damage to the germinal matrix.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the study was a retrospective comparative case series with a small sample size. Previous investigations [ 3 7 , 13 , 17 ] of mini-hook plate fixation were also retrospective case studies because the incidence of phalangeal avulsion fractures is relatively low, and there was insufficient evidence for planning a prospective study. A larger-scale, prospective study is necessary to support our results and obtain more outcome data.…”
Section: Discussionmentioning
confidence: 99%